2020
DOI: 10.3390/ijms21114008
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Pan-PDE Inhibitor Exerts Anti-Fibrotic Effects in Human Lung Fibroblasts via Inhibition of TGF-β Signaling and Activation of cAMP/PKA Signaling

Abstract: Phosphodiesterase (PDE) inhibitors are currently a widespread and extensively studied group of anti-inflammatory and anti-fibrotic compounds which may find use in the treatment of numerous lung diseases, including asthma and chronic obstructive pulmonary disease. Several PDE inhibitors are currently in clinical development, and some of them, e.g., roflumilast, are already recommended for clinical use. Due to numerous reports indicating that elevated intracellular cAMP levels may contribute to the alleviation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…Wójcik-Pszczoła and coauthors [ 33 ] used three different 7,8-disubstituted purine-2,6-dione derivatives (compound “832”—a pan-selective PDE inhibitor, compound “869”—a TRPA1 modulator and compound “145”—a pan-selective PDE inhibitor and a TRPA1 modulator) and evaluated their ability to inhibit the pro-fibrotic responses of lung fibroblast cell lines and MRC-5 104 cells once activated by TGF-β1 or FBS. In parallel, they studied their proliferation, migration, contraction, expression of profibrotic genes and phenotypic transition into myofibroblasts.…”
Section: Cyclic Nucleotide Pathway In Inflammation and Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…Wójcik-Pszczoła and coauthors [ 33 ] used three different 7,8-disubstituted purine-2,6-dione derivatives (compound “832”—a pan-selective PDE inhibitor, compound “869”—a TRPA1 modulator and compound “145”—a pan-selective PDE inhibitor and a TRPA1 modulator) and evaluated their ability to inhibit the pro-fibrotic responses of lung fibroblast cell lines and MRC-5 104 cells once activated by TGF-β1 or FBS. In parallel, they studied their proliferation, migration, contraction, expression of profibrotic genes and phenotypic transition into myofibroblasts.…”
Section: Cyclic Nucleotide Pathway In Inflammation and Fibrosismentioning
confidence: 99%
“…These data suggest that the TGF-β pathway is an important target for PDE inhibitors, which leads to inhibitory effects on cellular responses involved in airway remodeling. These potent pan-selective PDE inhibitors represent promising anti-remodeling drug candidates for further research, including research on anti-COVID-19 drugs [ 33 ]. Among these pan-selective compounds, sulindac, originally used as anti-inflammatory drug, was shown to be a PDE5 and PDE10 inhibitor [ 46 ].…”
Section: Cyclic Nucleotide Pathway In Inflammation and Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“… 18 A group of potent, pan-PDE inhibitors from the group of 7.8-disubstituted purine-2,6-dione derivatives represent promising anti-remodelling drug candidates for further research. 96 …”
Section: Novel Prospective With Pde Inhibitors In Asthmamentioning
confidence: 99%
“…We found that NE acted to antagonize latent TGFβ1 expression via a cAMP-PKA-CREB signaling axis. Activation of CREB through the use of phosphodiesterase inhibitors has previously been shown to antagonize fibrotic expression of lung and cardiac fibroblasts (Miller et al, 2011;Wójcik-Pszczoła et al, 2020) as well as cardiac fibrosis in a pressure overload mouse model (Gong et al, 2014) , suggesting a potential mechano-responsiveness of this mechanism. Simulated fibroblast responses to TGFβ1 indicated a synergistic response under tension with latent TGFβ1 activation and output expression occurring for lower input doses.…”
Section: Crosstalk Between Biochemical and Biomechanical Factors In Fmentioning
confidence: 99%